Mulching, rhizobial inoculation, and water supply shape soil enzyme activities and nutrient dynamics in a Namibian sandy soil under cowpea cultivation - Elisa Karina Albrecht; Simran Sekhri; Barbara Reinhold-Hurek; Shanmugam Solaiyappan Mani; Svenja C. Stock; Michaela A. Dippold; Annette Eschenbach; Joscha N. Becker (Plant and Soil, 2026)
Background and aims Agricultural soils in semi-arid sub-Saharan Africa are often low in soil organic carbon (SOC) and nitrogen (N), making them vulnerable to degradation and threatening food security of smallholder farmers. Conservation agriculture practices such as mulching are promoted as climate-resilient strategies to improve soil fertility, but it remains unclear whether these practices improve soil biogeochemical properties in semi-arid regions. Methods We conducted a greenhouse experiment that simulated a cowpea ( Vigna unguiculata ) growth period, a regional key crop, under water optimum and stress conditions using sandy soil from the Omusati region in Namibia. Effects of different mulches (wheat straw, wood chips, 1:1 mixture), inoculation with a locally adapted Bradyrhizobium and water conditions on soil biogeochemical properties, including SOC, N, microbial biomass and enzyme kinetics (β-glucosidase, chitinase, leucine-aminopeptidase) were investigated. Results We showed that mulching had limited short-term effects on SOC and N. Inoculation with rhizobia increased soil N, lowered C:N ratios and reduced N-related enzyme activities, demonstrating its potential to mitigate N limitation. Water stress decreased enzyme activities by 64%, indicating that water availability may outweigh management effects. Inoculation shifted the microbial demand from N towards C under water optimum, whereas all soils were N limited under water stress, reflected in enzymatic C:N ratios. Conclusion Our findings highlight cowpea inoculation as an effective strategy to improve soil N, while mulching provides additional benefits for soil fertility only under favourable water conditions. Increased C and N contents show that combining inoculated legumes with mulching can enhance nutrient availability in semi-arid agroecosystems, contributing to sustainable land management.